Tytul - Author, Author (Pedagogical Discourse, 2025)
The article analyses the concept of «idiom» or «phraseological unit» as defined by various researchers and scholars in the field of linguistics, which is the object of this study, characterises the peculiarities of using English idioms to develop learners’ lexical competences with the help of effective methodological approaches to improve the level of foreign language communication. The relevance of the work is related to the possibility of applying methodological approaches to the use of phraseological units in speech for the development of lexical and communicative competences, as well as the development of both cultural and social status. The article also notes that the use of English phraseological units will make the language more expressive, vivid, and emotionally coloured. Every nation and people reflects its vision of the world, its own way of life, traditions, culture and mentality in its phraseology. The research is descriptive and explanatory in nature. The study examines the main types of classifications of phraseological units, their meaning and translation. Specific examples are used to demonstrate the importance of correct translation of phraseological units not only for accurate understanding, but also for cultural enrichment. It is explained that it is necessary to use both non-communicative and communicative exercises in English lessons. A list of exercises for the development of lexical competences to improve the level of oral and written English is provided. The need to introduce different types of tasks using idioms and to update student’s books, textbooks with a certain number of idioms according to the level is emphasised. The results of the work can be used by educators of pre-university and higher education institutions who are interested in effective and modern ways of teaching and learning foreign languages.